Understanding Innovations in Journalistic Practice: A Field Experiment Examining Motivations for Fact‐Checking. (8th January 2016) - Graves, Lucas; Nyhan, Brendan; Reifler, Jason
Abstract : Why has fact‐checking spread so quickly within U.S. political journalism? In the first field experiment conducted among reporters, we varied journalist exposure to messages that highlight either audience demand for fact‐checking or the prestige it enjoys within the profession. Our results indicate that messages promoting the high status and journalistic values of fact‐checking increased the prevalence of fact‐checking coverage, while messages about audience demand were somewhat less successful. These findings suggest that political fact‐checking is driven primarily by professional motives within journalism, a finding that helps us understand the process by which the practice spreads within the press as well as the factors that influence the behavior of journalists.